16S rDNA sequencing combined with metabolomic probes to investigate the effects of Salmonella Pullorum on gut microbes and metabolites in broilers - Wu, Jiongwen; Xue, Ruixiang; Fan, Zhexia; Li, Ruina; Wang, Xiaomeng; Ye, Chutian; Chen, Shuya; Fang, Cheng; Zhang, Xiquan; Luo, Qingbin (Frontiers in Microbiology, 2025)
Pullorum disease (PD) caused by Salmonella Pullorum (SP) results in high mortality in chicks and potential carriers in adult chickens, negatively affecting growth and egg production. This study identified SP infection in 100-day-old White Plymouth Rock hens by serum plate agglutination and fecal and anal swab polymerase chain reaction. SP-infected broilers were classified into positive (P) and negative (N) groups using hematoxylin-and-eosin staining, metabolome sequencing, and 16S rDNA to investigate the effects of SP infection on the metabolites and microorganisms in the cecum of broilers. Groups had different degrees of inflammatory cell infiltration in the cecum, spleen, liver, and lung tissues. The diversity of bacterial flora in the cecum of Groups P and N differed significantly (P < 0.05). o__Lactobacillales and o__Verrucomicrobiota were significantly higher in Group P than in Group N (P < 0.05). At the genus level, g__Akkermansia was significantly higher in Group N (P < 0.05). Metabolome sequencing of cecum contents in Groups P and N screened 77 differential metabolites at the secondary metabolite level. 11 metabolites, including 2,4-dimethylbenzaldehyde, 3a,6b,7b,12a-tetrahydroxy-5b-cholanoic acid, and LysoPG 19:1, were differentially expressed in Group P (P < 0.05). A combined analysis of 16S rDNA sequencing and cecal content metabolomics identified 28 genera significantly associated with 38 metabolites in the cecum (P < 0.05). Specific bacterial genera such as Corynebacterium and Roseobacter have particularly prominent effects on metabolites. These findings highlight the significant alterations in gut microbial composition and metabolic functions due to SP infection. The differential metabolites and bacterial taxa identified in this study may provide insights into the underlying mechanisms of PD pathogenesis and potential biomarkers for disease management.